2016
DOI: 10.1371/journal.pone.0165931
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Common Mental Disorders among Ethiopian Youth: Structural Equation Modeling

Abstract: BackgroundAlthough the consequences of food insecurity on physical health and nutritional status of youth living have been reported, its effect on their mental health remains less investigated in developing countries. The aim of this study was to examine the pathways through which food insecurity is associated with poor mental health status among youth living in Ethiopia.MethodsWe used data from Jimma Longitudinal Family Survey of Youth (JLFSY) collected in 2009/10. A total of 1,521 youth were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
36
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 76 publications
8
36
0
2
Order By: Relevance
“…The present study also shows teenage girls from socio-economically disadvantaged groups (schedule caste/schedule tribe) with a low family income (first and second terciles) were more likely to have mental health issues, which accords with previous studies [8,53,54]. For example, a systematic review paper reported socioeconomically disadvantaged adolescents with a persistent low socioeconomic status were more likely to develop mental health problems [53], and Dashiff et al [54] reported poverty has direct effects on adolescent mental health.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study also shows teenage girls from socio-economically disadvantaged groups (schedule caste/schedule tribe) with a low family income (first and second terciles) were more likely to have mental health issues, which accords with previous studies [8,53,54]. For example, a systematic review paper reported socioeconomically disadvantaged adolescents with a persistent low socioeconomic status were more likely to develop mental health problems [53], and Dashiff et al [54] reported poverty has direct effects on adolescent mental health.…”
Section: Discussionsupporting
confidence: 92%
“…After controlling for potential confounders, multivariate analysis showed household food insecurity was strongly associated with high anxiety, high depression, high loss of behavioral control and high psychological distress, which are consistent with the findings of many other studies [7,8,9,26,43]. Although no casual mechanism between FI and negative mental health has been established for adolescents, it has been suggested that uncertainty regarding the maintenance of food supplies generates stresses that might contribute to negative outcomes [59,60].…”
Section: Discussionsupporting
confidence: 90%
“…As in any other LMICs, the prevalence and burden of anxiety and depression in Ethiopia is high. For example, a systematic review and meta-analysis study reported that the pooled prevalence of these disorders is 22% [14], which is associated with risk factors such as food insecurity [15], poverty, violence, migration, and substance use [16]. The burden of depression alone contributes to about 6.5% of the burden of diseases [16], however, as noted above few people are able to receive formal mental health services.…”
Section: Introductionmentioning
confidence: 99%
“…As in any other LMICs, the prevalence and burden of anxiety and depression in Ethiopia is high. For example, a systematic review and meta-analysis study reported that the pooled prevalence of these disorders is 22% (14), which is associated with risk factors such as food insecurity (15), poverty, violence, migration, and substance use (16). The burden of depression alone contributes to about 6.5% of the burden of diseases (16), however, as noted above few people are able to receive formal mental health services.…”
mentioning
confidence: 99%